Formative research on the instructional design process of virtual reality (VR)-based learning environments - Chen, Chwen Jen (2007)
To date, the educational benefits offered by the virtual reality (VR) technology are generally well accepted. Indeed, many efforts are underway to explore ways, both theoretically and practically, to produce effective virtual reality learning. Chen, Toh and Wan (2004), for instance, have proposed an instructional design model that prescribes instructional methods for guiding the design of VR based learning environments. Although this model serves as a feasible and useful template to guide the design of VR based learning environments, particularly learning environments that adopt the constructivist paradigm of instruction, there are still rooms to enhance its robustness. This paper describes how formative research method can be used to improve this instructional design model. Formative research, which is qualitative in nature, is a method that has been employed to develop as well as to improve design theories (or models). The paper also reports some preliminary findings of the study.